Analisis Parameter pH, BOD, TSS, Minyak Dan Lemak Serta Total Coliform Pada Limbah Cair Rumah Sakit Gerbang Sehat Long Bagun Mahakam Ulu - Fachruddin Azwari; Kemala Hadidjah; Christine Elia Benedicta; Rusli Wahyuni (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Public welfare is measured one of which is from public health which is supported through hospital health services, the amount of liquid waste produced. Liquid waste or hospital wastewater can cause environmental pollution. Therefore, it is necessary to treat waste using a Wastewater Treatment Plant (WTP). The purpose of this study was to determine the wastewater content after treatment through WTP with wastewater quality analysis at the Gerbang Sehat Mahulu Hospital at Long Bagun District, Mahakam Ulu Regency. The stages of research carried out are field observations, collecting wastewater samples from WTP output of Mahulu Healthy Gate Hospital and analysis of wastewater content in the laboratory including pH, BOD, TSS, oil and fat, and total coliform. The results of liquid waste are adjusted to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia (RI) No.68 of 2016. From the results of the study, the value of the quality content of liquid waste with parameters of pH, BOD, TSS, oil, and fat and the total coliform has been below the standard quality so that it is suitable for release to the environment.